Black Feminism Reimagined : After Intersectionality - Nash, Jennifer C., 1980- (Book collections on Project MUSE., 2019)
"In Black Feminism Reimagined Jennifer C. Nash reframes black feminism's engagement with intersectionality, often celebrated as its primary intellectual and political contribution to feminist theory. Charting the institutional history and contemporary uses of intersectionality in the academy, Nash outlines how women's studies has both elevated intersectionality to the discipline's primary program-building initiative and cast intersectionality as a threat to feminism's coherence. As intersectionality has become a central feminist preoccupation, Nash argues that black feminism has been marked by a single affect--defensiveness--manifested by efforts to police intersectionality's usages and circulations. Nash contends that only by letting go of this deeply alluring protectionist stance, the desire to make property of knowledge, can black feminists reimagine intellectual production in ways that unleash black feminist theory's visionary world-making possibilities." -- Publisher's description